Karachay-Balkarian toponymy as a means of accumulation and storage of ethnocultural information - Bashieva, Svetlana K.; Bakhtikireeva, Uldanai M. (The New Research of Tuva, 2025)
The article examines Karachay-Balkar toponyms that contain ethnocultural information. The groups of toponyms based on associative connections with religious life, historical events, interethnic contacts, spiritual culture, natural resources, and similar factors possess the most distinct ethnocultural content. The research is based on 123 geographical object names recorded in various publications. The toponyms are analyzed according to the types of ethnocultural information verbalized in the geographical names, which are categorized into groups. The first group demonstrates that, prior to the adoption of Islam by the Karachays and Balkars, their beliefs constituted a mixture of elements of medieval Christianity with primitive religious notions and rituals. The pagan beliefs of the Karachays and Balkars are primarily associated with Tengrism, which played a significant role in shaping ancient Turkic culture. The second group reflects historical events that took place in Karachay-Balkaria. The third group illustrates interethnic contacts in the region, which were shaped by labor migration, trade relations, and mixed marriages.